The mysterious abductions - Hecht, Tracey; Liebman, Kate (2016)
Three unlikely nocturnal animal friends--Dawn the fox, Tobin the pangolin, and Bismark the sugar glider--form a brigade of the night to look into the mysterious disappearance of animals
Ages 7-11
Keywords: Nocturnal animals -- Juvenile fiction